Online Pajak: Penggunaan dan Pelaporan - Sinubu, Michelle (Jurnal Riset Akuntansi Solvency, 2025)
The purpose of this research is to analyse the use of the efilling system and the obligation to pay taxes. The analytical method used in this thesis research is a descriptive approach. which has the aim of analyzing, then a conclusion is drawn and the type of research used is descriptive qualitative research. The research findings indicate a annual tax return reporting at the Faculty of Public Health, Sam Ratulangi University Manado, employees and lecturers in reporting tax returns, in the efilling system sometimes there are those who are late or forget, do not understand, so they need the services of others. The limitation of this research is that this research is focused on the online tax reporting system. by using the e-Filing application to submit Annual Tax Return for individual taxpayers. The limitation of this research is that this research is focused on the online tax reporting system. by using the e-Filing application to submit Annual Tax Return for individual taxpayers. Online tax was developed to support the implementation of reporting for taxpayers, especially individual taxes. By investigating the application and effects of this application for individual taxpayers, this study aims to find out how the use of the efilling system and the obligation to pay taxes